Standardization of lateral pelvic radiograph is necessary to predict spinopelvic mobility accurately. (July 2020) - Ransone, Michael; Fehring, Keith; Fehring, Thomas
Abstract : Aims: Patients with abnormal spinopelvic mobility are at increased risk for instability. Measuring the change in sacral slope (ΔSS) can help determine spinopelvic mobility preoperatively. Sacral slope (SS) should decrease at least 10° to demonstrate adequate posterior pelvic tilt. There is potential for different ΔSS measurements in the same patient based on sitting posture. The purpose of this study was to determine the effect of sitting posture on the ΔSS in patients undergoing total hip arthroplasty (THA). Methods: In total, 51 patients undergoing THA were reviewed to quantify the variability in preoperative spinopelvic mobility when measuring two different sitting positions using SS for planning. Results: A total of 32 patients had standardized relaxed sitting radiographs, while 35 patients had standardized flexed sitting images. Of the 32 patients with relaxed sitting views, the mean ΔSS was 20.7° (SD 8.9°). No patients exhibited an increase in SS during relaxed sitting (i.e. anterior pelvic tilt or so-called reverse accommodation). Of the 35 patients with flexed sitting radiographs, the mean ΔSS was only 2.1° (SD 9.7°) with 16/35 (45.71%) showing anterior pelvic tilt, or so-called reverse accommodation, unexpectedly increasing the sitting SS compared to the standing SS. Overall, 18 patients had both relaxed sitting and flexed sitting radiographs. In patients with both types of sitting radiographs, the mean relaxed sit to stand ΔSS was 18.06° (SD 6.07°), while only a 3.00° (SD 10.53°) ΔSS was noted when flexed sitting. There was a mean ΔSS difference of 15.06° (SD 7.67°) noted in the same patient cohort depending on sitting posture (p < 0.001). Conclusion: A 15° mean difference was noted depending on the sitting posture of the patient. Since decisions on component position can be made on preoperative lateral sit-stand radiographs, postural standardization is crucial. If using ΔSS for preoperative planning, the relaxed sitting radiograph is preferred. Cite this article: Bone Joint J 2020;102-B(7 Supple B):41–46.